KOLABORASI PENDIDIK DENGAN ORANG TUA DALAM MENINGKATKAN PRESTASI PESERTA DIDIK - Rinaldi Datunsolang; Putriani L. Maliki (Irfani (e-Journal), 2023)
This article aims to see how the collaboration of educators and parents improves student achievement. The method used in this research is a library research study where the data in this research is constructed from various literature, both online and in print. Then the data is classified and analyzed using a philosophical approach. The results of the study found that in the collaboration carried out by educators and parents there were several models that could be used as a solution to improve student achievement, namely visits to students' homes, inviting parents to school, holding correspondence between school and family, mutual support between educators and parents